Long-term effects of liquid nanoparticles on algal growth and photosynthetic biogas upgrading - de Mello, Bruna Sampaio [UNESP]; Sarti, Arnaldo [UNESP]; Muñoz, Raúl (Elsevier, 2025)
Photosynthetic biogas upgrading relies on a microalgal–bacterial consortium that simultaneously removes CO2 and H2S from biogas. However, the process still faces a few challenges. In this context, the performance of a pilot high-rate algal pond devoted to photosynthetic biogas upgrading and nutrient valorization from real digestate supplemented with carbon-coated zero-valent iron liquid nanoparticles (L-NPs) was evaluated. Additionally, the influence of the biogas flowrate (55, 75 and 95 L d−1) on photosynthetic biogas upgrading performance was assessed. The addition of 2 mL L−1 of L-NPs, combined with intensive biomass harvesting, promoted higher biomass productivity (89 g m−2 d−1) without negatively impacting algal photosynthetic activity or biogas upgrading performance. The presence of soluble organic carbon in the L-NPs suggested that the biostimulation of microalgal growth supported the high algal biomass productivities recorded. At the highest biogas flowrate (75 and 95 L d−1), an increased CO2 and CH4 content in the upgraded biogas was achieved due to a reduced contact time between the recirculating cultivation broth and the biogas, which minimized the stripping of N2 and O2. Moreover, the biomethane reached CH4 concentrations of 94.9 % (v/v) and low levels of CO2 (2.1 %), O2 (0.4 %), and N2 (2.6 %) at biogas flowrate of 75 L d−1.